Influences of cultural capital and internationalization on global competence in higher education: a systematic literature review - Teng, Yiying; Cosier, Meghan E. (Frontiers in Education, 2024)
Introduction In an increasingly global economy, the global competence of students in higher education is a critical area of importance. The purpose of the study was to explore the research on factors that influence an individual’s global competence in both international and Chinese contexts. Methods Under the umbrella of cultural capital theory and Internationalization, a systematic literature review analyzed and synthesized the empirical studies of global competence from 2013 to 2022. Results This research revealed that students with higher cultural capital backgrounds obtain more educational opportunities and further exhibit better global competence achievement. Internationalization abroad is a direct and practical pedagogy for global competence acquisition, reflected in student and faculty mobility. Internationalization opportunities in an individual’s home country catalyze global competence. Conclusion These results highlight that students who have a lower capital background or few opportunities for mobility can reap the potential benefits of global competence attainment through involvement in domestic educational activities.